Recent progress in research on cell-to-cell movement of rice viruses - Hiraguri, Akihiro; Netsu, Osamu; Sasaki, Nobumitsu; Nyunoya, Hiroshi; Sasaya, Takahide (Frontiers in Microbiology, 2014)
To adapt to plants as hosts, plant viruses have evolutionally needed the capacity to modify the host plasmodesmata (PD) that connect adjacent cells. Plant viruses have acquired one or more genes that encode movement proteins (MPs), which facilitate the cell-to-cell movement of infectious virus entities through PD to adjacent cells. Because of the diversity in their genome organization and in their coding sequences, rice viruses may each have a distinct cell-to-cell movement strategy. The complexity of their unusual genome organizations and replication strategies has so far hampered reverse genetic research on their genome in efforts to investigate virally encoded proteins that are involved in viral movement. However, the MP of a particular virus can complement defects in cell-to-cell movement of other distantly related or even unrelated viruses. Trans-complementation experiments using a combination of a movement-defective virus and viral proteins of interest to identify MPs of several rice viruses have recently been successful. In this article, we review recent research that has advanced our understanding of cell-to-cell movement of rice viruses.